2014
DOI: 10.1039/c4nr01544d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fullerenol surface chemistry on nanoparticle binding-induced protein misfolding

Abstract: Fullerene and its derivatives with different surface chemistry have great potential in biomedical applications. Accordingly, it is important to delineate the impact of these carbon-based nanoparticles on protein structure, dynamics, and subsequently function. Here, we focused on the effect of hydroxylation - a common strategy for solubilizing and functionalizing fullerene - on protein-nanoparticle interactions using a model protein, ubiquitin. We applied a set of complementary computational modeling methods, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 63 publications
(71 reference statements)
1
44
0
Order By: Relevance
“…DMD is special type of molecular dynamic simulation algorithm with enhanced sampling efficiency, which has been extensively used to model protein folding, protein-ligand interactions as well as protein-nanoparticle interactions 7, 33 . We adopt a united-atom representation of simulated molecules, where all heavy atoms and polar hydrogens are explicitly modelled.…”
Section: Methodsmentioning
confidence: 99%
“…DMD is special type of molecular dynamic simulation algorithm with enhanced sampling efficiency, which has been extensively used to model protein folding, protein-ligand interactions as well as protein-nanoparticle interactions 7, 33 . We adopt a united-atom representation of simulated molecules, where all heavy atoms and polar hydrogens are explicitly modelled.…”
Section: Methodsmentioning
confidence: 99%
“…Elevated level of reactive oxygen species (ROS) could be a possibility, as well as the misfolding of proteins by NP binding. It begins to be documented that protein conformational changes can occur at the NP surface at the secondary or tertiary levels (Shao et al, 2011;SimonVazquez et al, 2014) and that the NP surface chemistry is decisive (Radic et al, 2014). Proteins forming the protein corona might be particularly affected.…”
Section: Is There a "Biological" Effect?mentioning
confidence: 96%
“…The accelerated sampling of DMD is well-suited characterization of binding properties in simulations, which requires study of many interactions. Radic et al [29] utilized DMD simulations to illustrate the effects of surface chemistry on the binding of nanoparticles to their target proteins. They demonstrated that highly hydroxylated fullerene nanoparticles form hydrogen bonds with protein surfaces, stabilizing them without inducing structural changes, while less hydroxylated fullerene particles are hydrophobic and can cause proteins to misfold.…”
Section: Surface Chemistrymentioning
confidence: 99%